Developing Teacher Competence Through Digital-Based Learning at the PGRI Ciamis Regency - Rahayu, Ayu Puji; Mulyani, Agustina; Permana, Fadilah; Jamilah, Jam Jam (Fakultas Kewirausahaan Universitas Garut, 2024)
The mastery of digital technology has become an essential skill for teachers in addressing the demands of 21st-century learning. However, many educators still face limitations in effectively utilizing technology in the learning process. This Community Service Program (PkM) was conducted to enhance teacher competencies through digital-based learning training at PGRI Kabupaten Ciamis. The method consisted of need analysis, module development, hands-on training sessions, and intensive mentoring. The results showed significant improvements in teachers' abilities to utilize digital platforms for planning, implementing, and evaluating learning activities. This program had a positive impact by improving teachers’ digital literacy and enabling the integration of technology into classroom practices. The initiative is expected to foster innovative, adaptive, and relevant learning in the digital era.